(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The article examines the influence of psychological factors on patients’ choice of aesthetic procedures. Key aspects are analyzed: level of self-esteem, age perception, social pressure, emotional state and expectations of treatment results. The importance of psychodiagnostics and an interdisciplinary approach in planning aesthetic therapy is emphasized. A conclusion is made about the need to individualize the strategy of interaction with the patient to improve the effectiveness and safety of the procedures.